Genetic complementation of propionyl-CoA carboxylase deficiency in cultured human fibroblasts. - Gravel, R A (1977)
Propionyl-CoA carboxylase (PCC) deficiency is an inherited metabolic disorder showing considerable variability of expression. We have investigated the possibility that there is a genetic basis for the clinical heterogeneity in this disorder by examining complementation in Sendai virus mediated heterokaryons of mutant fibroblast strains. Restoration of PCC activity was monitored in individual multinucleate cells in situ using a radioautographic procedure which detects the incorporation of 14C-propionate into trichloracetic acid precipitable material. Each mutant strain incorporated negligible amounts of radioactivity compared to control strains. Activity was not restored when different mutants were mixed without virus or when homokaryons were produced by self-fusion. Seven mutant strains were fused in all pairwise combinations and examined for increased 14C-propionate incorporation in heterokaryons. Two main complementation groups were revealed. One group was composed of three mutants. The other was a complex group composed of four mutants in which intragroup complementation was demonstrated. Two mutants showing excellent complementation by radioautography were examined for complementation by the direct assay of PCC ACTIVITY. The enzyme activity of virus-treated preparations with 23% multinucleate cells was 183 U (pmol/min/mg protein) compared to 16 U for the untreated mixture (normal range 450-850 u). We conclude that PCC deficiency resulted from mutations of heterogeneous origin, although the classification of mutants into complementation groups did not correlate with patterns of clinical heterogeneity.